Menakar Tantangan dan Potensi Jurusan Bahasa dan Sastra Arab (BSA) IAIN Syekh Nurjati Cirebon di Era Pendidikan 4.0 - Gazali, Erfan (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This article discusses the readiness of the Department of Arabic Literature IAIN Syeikh Nurjati Cirebon in dealing with the development of education in the era of the industrial revolution 4.0. Descriptive-analytical method was chosen as the type of research with the stages of analyzing data including: data collection, data reduction, and drawing conclusions or verification. The level of competition based on the excellence of human resources in the era of the industrial revolution 4.0 requires all countries to move quickly in enhancing their human resources, actively contributing to the generation of superior and competitive generation as part of a knowledge-based society making responsibilities that cannot be avoided by higher education institutions. the level of education has risen to become a producer of innovation as a reflection of the educational era 4.0. Exploring all the potentials of the Arabic language and literature department of IAIN Syeikh Nurjati Cirebon and the challenges that will be faced in the era of education 4.0 will be the aim of this study. Cirebon is an area with a rich history and pluralistic culture supported by the existence of the kraton along with hundreds of manuscripts has made this area a field of knowledge and research that is very potential for the development of Arabic language and literary knowledge in Indonesia.